PENGARUH TRAINING AND DEVELOPMENT, SERVANT LEADERSHIP, DAN REWARD TERHADAP EMPLOYEE RETENTION DI MEDIASI OLEH EMPLOYEE ENGAGEMENT PADA RESTORAN DI KOTA BATAM - Nelson, Alden; Kurnaedi, Julius (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This research aims to analyze the influence of training and development, servant leadership, and rewards on employee retention, mediated by employee engagement in restaurants in Batam City. In obtaining data, this research used a random sampling method and questionnaires were distributed to 381 respondents in restaurants in Batam City. In analyzing the research data, the SPSS application was used for multiple linear regression analysis and Smart-PLS was used to analyze the relationship data between dependent and independent variables to process the data that had been distributed. The results of this research show that the servant leadership and reward variables have a direct effect on employee retention which is mediated by employee engagement, while the training and development variables do not have a direct effect on employee retention or are mediated by employee engagement.